Complete genome sequence of Pyrobaculum oguniense. Issue 3 (May 2012) - Bernick, David; Karplus, Kevin; Lui, Lauren; Coker, Joanna; Murphy, Julie; Chan, Patricia; Cozen, Aaron; Lowe, Todd
Abstract Pyrobaculum oguniense TE7 is an aerobic hyperthermophilic crenarchaeon isolated from a hot spring in Japan. Here we describe its main chromosome of 2, 436, 033 bp, with three large-scale inversions and an extra-chromosomal element of 16, 887 bp. We have annotated 2, 800 protein-coding genes and 145 RNA genes in this genome, including nine H/ACA-like small RNA, 83 predicted C/D box small RNA, and 47 transfer RNA genes. Comparative analyses with the closest known relative, the anaerobePyrobaculum arsenaticum from Italy, reveals unexpectedly high synteny and nucleotide identity between these two geographically distant species. Deep sequencing of a mixture of genomic DNA from multiple cells has illuminated some of the genome dynamics potentially shared with other species in this genus.